Geologic overview of the Mars Science Laboratory rover mission at the Kimberley, Gale crater, Mars. Issue 1 (28th January 2017) - Rice, Melissa S.; Gupta, Sanjeev; Treiman, Allan H.; Stack, Kathryn M.; Calef, Fred; Edgar, Lauren A.; Grotzinger, John; Lanza, Nina; Le Deit, Laetitia; Lasue, Jeremie; Siebach, Kirsten L.; Vasavada, Ashwin; et al.
Abstract: The Mars Science Laboratory (MSL) Curiosity rover completed a detailed investigation at the Kimberley waypoint within Gale crater from sols 571–634 using its full science instrument payload. From orbital images examined early in the Curiosity mission, the Kimberley region had been identified as a high‐priority science target based on its clear stratigraphic relationships in a layered sedimentary sequence that had been exposed by differential erosion. Observations of the stratigraphic sequence at the Kimberley made by Curiosity are consistent with deposition in a prograding, fluvio‐deltaic system during the late Noachian to early Hesperian, prior to the existence of most of Mount Sharp. Geochemical and mineralogic analyses suggest that sediment deposition likely took place under cold conditions with relatively low water‐to‐rock ratios. Based on elevated K2 O abundances throughout the Kimberley formation, an alkali feldspar protolith is likely one of several igneous sources from which the sediments were derived. After deposition, the rocks underwent multiple episodes of diagenetic alteration with different aqueous chemistries and redox conditions, as evidenced by the presence of Ca‐sulfate veins, Mn‐oxide fracture fills, and erosion‐resistant nodules. More recently, the Kimberley has been subject to significant aeolian abrasion and removal of sediments to create modern topography that slopes away from Mount Sharp, a process that has continued to the present day. Key Points: Mars Science Laboratory explored the Kimberley waypoint from sols 571–634 using its full science instrument payload The stratigraphic sequence most likely formed at the margins of a lake within Gale crater, prior to the existence of Mount Sharp The sediments at the Kimberley were derived from several igneous sources, including an alkali feldspar protolith